Starter villain - Scalzi, John, 1969- (Tor Publishing Group, 2023)
"Inheriting your uncle's supervillain business is more complicated than you might think. Particularly when you discover who's running the place. Charlie's life is going nowhere fast. A divorced substitute teacher living with his cat in a house his siblings want to sell, all he wants is to open a pub downtown, if only the bank will approve his loan. Then his long-lost uncle Jake dies and leaves his supervillain business (complete with island volcano lair) to Charlie. But becoming a supervillain isn't all giant laser death rays and lava pits. Jake had enemies, and now they're coming after Charlie. His uncle might have been a stand-up, old-fashioned kind of villain, but these are the real thing: rich, soulless predators backed by multinational corporations and venture capital. It's up to Charlie to win the war his uncle started against a league of supervillains. But with unionized dolphins, hyper-intelligent talking spy cats, and a terrifying henchperson at his side, going bad is starting to look pretty good. In a dog-eat-dog world...be a cat"--